Kronotop dan Sinkretisme: Kajian Dialogis Budaya dan Agama pada Upacara Rambu Solo Masyarakat Tana Toraja. - Nurhakki; Bahfiarti, Tuti; Aziz, Syamsuddin (LP2M IAIN Palopo, 2025)
This article aims to analyze the phenomenon of syncretism in the Rambu Solo ceremony in Tana Toraja, focusing on the chronotope of communication in the syncretism process bound by the dimensions of space and time. The research method used is a qualitative approach with a communication ethnography design, which involves data collection through participatory observation, in-depth interviews, and focus group discussions (FGD). The data obtained were analyzed using thematic and narrative analysis techniques to identify the main themes that emerged in the social and cultural interactions of the Toraja people. This approach allowsresearchers to explore in depth the meaning and process of symbol negotiation in the Rambu Solo ritual. The results of this study, Chronotope plays an important role as a concept that binds space and time in the Rambu Solo ceremony, a death ritual that becomes a dialogical arena combining various aspects of social and religious life. This shows a real manifestation of kinship ties that arebound in space and time with ancestors that are passed down from generation to generation, as well as religious ties to divine power, both of which encourage cultural and religious syncretism. The syncretism that occurs is dynamic and dialogical, not a meaningless unification, but rather a process of interaction that maintains cultural identity rooted in the local religion of aluk todolo in dialectic with religious teachings as the official discourse of the state. This study emphasizes the importance of a dialogical and interdisciplinary approach in understanding complex cultural phenomena, especially those involving the dimensions of space, time, and religiosity in the contextof indigenous communities. Keywords: Chronotope, Syncretism, Dialogue, Rambu Solo